High-capacity multi-layer chip ceramic capacitor with X6S characteristic and preparation method of high-capacity multi-layer chip ceramic capacitor
By using BaTiO3-Mn3O4-MgCO3-D2O3-BaCO3-Nb2O5-V2O5 system and dopants in dielectric ceramic materials, the shell-core structure is solved, and the insulation resistance deterioration and temperature stability of existing dielectric ceramic materials are solved at high temperatures. The poor performance problem achieves the effect of high capacity and low dielectric loss factor.
Patent Information
- Application Number
- CN202411802833.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-09
AI Technical Summary
When the existing dielectric ceramic materials apply an electric field at high temperature, the insulation resistance of the non-reduced laminated ceramic capacitors is likely to deteriorate significantly, and the dielectric constant varies greatly at different temperatures, resulting in poor capacity and temperature stability.
The dielectric ceramic materials were prepared by BaTiO3-Mn3O4-MgCO3-D2O3-BaCO3-Nb2O5-V2O5 system. By adding a small amount of submicron or nanoscale dopants and rare earth oxides to the solid-phase method synthesized barium titanate, the formation of Shell-core structure inhibits the growth of barium titanate grains and improves temperature characteristics.
It realizes that dielectric ceramic materials maintain high insulation resistivity and low dielectric loss factor under high temperature environments, and combines good temperature stability and high capacity.
Smart Images

Figure CN119400593A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic capacitors, and in particular to a high-capacitance multilayer chip ceramic capacitor with X6S characteristics and a preparation method thereof. Background Art
[0002] Multilayer ceramic capacitors (MLCC) are chip capacitors suitable for SMT surface mounting, and are required for almost all electronic devices. In particular, the demand for MLCCs in mobile communication products, computers, digital cameras, and new-generation digital home appliances is increasing day by day. Moreover, as electronic devices tend to be lighter, thinner, shorter, and smaller, and as surface mounting technology becomes more and more popular, the development of MLCCs has more potential, and is constantly expanding in the direction of miniaturization, high capacity, and high stability.
[0003] As the application scenarios of MLCC continue to increase, the performance requirements of MLCC are becoming more and more diversified. The Electronic Industries Association (EIA) of the United States has formulated the X6S specification for high temperature capacitors, requiring capacitors to have high dielectric constants and good temperature stability in the temperature range of -55℃ to 105℃ (the capacity change range is less than ±22% compared to 25℃). Barium titanate (BaTiO3) has a high dielectric constant and is currently the main material for preparing high-capacitance multilayer ceramic capacitors, but the dielectric properties of pure BaTiO3 vary greatly at different temperatures. The dielectric constant varies relatively flat with temperature at room temperature of 25℃, and the dielectric constant in the high temperature zone varies greatly with temperature, with a peak at the Curie point (125℃). The poor temperature stability of the capacity requires the introduction of modified additives to improve the temperature stability of the capacity. Existing dielectric ceramic materials use barium titanate as the main component and are doped with oxides of zirconium, barium, manganese and silicon, but when an electric field is applied at high temperature, it is easy to cause the insulation resistance (IR) of the non-reducible multilayer ceramic capacitor to deteriorate significantly. That is to say, existing dielectric ceramic materials have the defects of short IR life and low reliability. Class I ceramics (CaZrO3, SrCaTiZrO3, Ca(TiZr)O3) can improve high temperature IR degradation and reliability problems, but Class I ceramics have a low dielectric constant (less than 100), so they cannot be used to prepare large-capacity capacitors. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a multilayer ceramic capacitor with X6S characteristics and high capacitance and a preparation method thereof to improve the high temperature IR degradation and reliability problems. The present invention has both X6S characteristic temperature stability and high capacitance, and it still has high IR characteristics and low dielectric loss factor (tanδ) even in a high temperature environment.
[0005] Based on the above purpose, the present invention provides a method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance, comprising the following steps:
[0006] S1, mixing and grinding barium titanate, a dopant, a dispersant, and a solvent to obtain a powder mixture slurry;
[0007] S2, adding a binder and a plasticizer to the mixture slurry to form a ceramic slurry;
[0008] S3, applying the obtained ceramic slurry to form a ceramic film;
[0009] S4, printing an inner electrode on the ceramic film;
[0010] S5, stacking the ceramic films printed with the inner electrode patterns to obtain a green embryo block;
[0011] S6, pressing the green embryo block to be compacted by isostatic hydropressure;
[0012] S7, cutting the compacted green embryo block to obtain a capacitor green embryo;
[0013] S8, removing the glue from the capacitor embryo to remove organic matter;
[0014] S9, sintering the capacitor green body after debinding into porcelain;
[0015] S10, rolling and chamfering the fired capacitor ceramic body to expose the inner electrode and reduce the surface stress of the ceramic body;
[0016] S11, copper-plating the two ends of the chamfered capacitor ceramic body to connect the inner and outer electrodes;
[0017] S12, sintering at 700-800℃ under nitrogen protection;
[0018] S13. Nickel and tin are sequentially plated on the copper end surface to obtain a high-capacitance multilayer ceramic capacitor with X6S characteristics.
[0019] Based on 100 parts by mass of barium titanate, the dopant includes the following components in parts by mass: 1.0-2.0 parts by mass of SiO2, 0.5-0.7 parts by mass of MgCO3, 0.04-0.06 parts by mass of Mn3O4, 1.5-2.5 parts by mass of BaCO3, 0.2-0.5 parts by mass of Nb2O5, 1.2-1.5 parts by mass of V2O5, and 0.8-1.2 parts by mass of rare earth oxide D2O3. If the dopant does not include the above-mentioned composition, the prepared dielectric ceramic material cannot meet the X6S standard and have good high temperature impedance characteristics and low dielectric loss factor.
[0020] In the rare earth oxide D2O3, D is any one or more of Y, Ho, Yb, Gd, and Dy.
[0021] The present invention adopts BaTiO3-Mn3O4-MgCO3-D2O3-BaCO3-Nb2O5-V2O5 system to prepare dielectric ceramic materials and capacitors thereof, adds a small amount of submicron or nanometer-level silicon, magnesium, manganese, calcium, niobium, vanadium compounds, and two or more of yttrium, ytterbium, and holmium element oxides to barium titanate synthesized by solid phase method, mixes them evenly by wet method, and evenly mixes them with a certain proportion of dispersant, plasticizer, and binder to obtain ceramic slurry, and prepares MLCC through a series of processes, during the calcination process of dielectric ceramics, some additives will promote the formation of shell-core structure of ceramic grains, inhibit the further growth of barium titanate grains, improve the temperature characteristics of dielectric ceramics, and its temperature stability meets the X6S dielectric material standard formulated by the American Electronics Industry Association. When barium titanate is sintered in a reducing atmosphere, it is easy to lose oxygen at high temperature and become a semiconductor. Magnesium, calcium, manganese and other compounds play an acceptor role in the calcination process of the ceramic medium, and the oxygen vacancy concentration caused is greater than the oxygen vacancy concentration formed by oxygen volatilization, so that barium titanate can also maintain a high electrical insulation resistivity when sintered in a reducing atmosphere. Therefore, the dielectric ceramic material of the present invention has both good high-temperature impedance characteristics and low dielectric loss factor (tanδ). At the same time, the reasonable sintering temperature and sintering atmosphere make the ceramic body have good density, suitable core-shell structure and uniform particle size, so that the prepared multilayer ceramic capacitor has excellent dielectric properties and capacitance-temperature characteristics.
[0022] The barium titanate accounts for 92-95 wt % of the total amount of the barium titanate and the dopant, and the amount of the dopant accounts for 15-8 wt % of the total amount of the barium titanate and the dopant.
[0023] The particle size of the BaTiO3 is 150-250nm and is prepared by a solid phase method.
[0024] The dispersant includes polyethylene oxide resin, and the amount of the dispersant added is 0.5 to 2 parts by mass. The dispersant is used to disperse the composition of the dielectric ceramic material. The dispersant of the present invention is not particularly limited, but in order to achieve the above-mentioned dispersion, the dispersant can be polyethylene oxide resin and other resins.
[0025] The solvent includes water, ethanol and / or toluene, and the added amount of the solvent is 60 to 80 parts by weight.
[0026] The grinding in S1 is performed using a ball mill, the grinding balls are 0.2-0.4 mm zirconium balls, the grinding speed is 40-80 rpm, and the grinding and mixing time is 4-6 hours.
[0027] The binder includes polyvinyl butyral resin, and the addition amount of the binder is 20 to 30 parts by mass; the plasticizer includes dioctyl adipate, and the addition amount of the plasticizer is 0.5 to 2 parts by mass. The binder of the present invention is not particularly limited, but for the purpose of achieving the aforementioned bonding, the binder can be polyvinyl butyral resin (PVB) and other resins. The plasticizer of the present invention is not particularly limited, but for the purpose of improving the plasticity of the ceramic slurry.
[0028] The third step, the fourth step, the fifth step, the sixth step, the seventh step and the eighth step of the present invention are common processes in the industry, and technicians in the industry can understand the practices of each step without detailed description of the present invention.
[0029] In the S9, the sintering temperature is 1265-1275°C, the sintering atmosphere is 1.8-2.2% H2-N2 by volume, and the sintering time is 1.7-2.3 hours. Preferably, the sintering temperature is 1270°C, the sintering atmosphere is 2% H2-N2, and the sintering time is 2 hours. It should be noted that if the sintering conditions are not within this range, the capacitor ceramic body cannot have good density, suitable core-shell structure and uniform particle size, so that the prepared multilayer ceramic capacitor cannot have excellent dielectric properties and capacitance-temperature characteristics.
[0030] The tenth, eleventh, twelfth and thirteenth steps of the present invention are common processes in the industry, and technicians in the industry can understand the steps without detailed description of the present invention. Among them, the sintering is carried out at 700-800°C under nitrogen protection, the purpose is to burn out the organic components in the copper end, improve the density of the copper end, and make the copper end and the ceramic body tightly connected.
[0031] The present invention also provides a multilayer ceramic capacitor with high capacitance and X6S characteristics, which is prepared by the preparation method described in the claims. It comprises a dielectric ceramic layer, an inner electrode layer and an outer electrode. The dielectric ceramic layer and the inner electrode layer overlap each other, and the inner electrode is electrically connected to the outer electrodes at both ends. The outer electrode is a multilayer structure, which is copper, nickel and tin from the inside to the outside. The capacitor of the present invention is of the specification of British standard number 0805, and the actual size is 2.00mm×1.25mm.
[0032] In the present invention, MgCO3:Mg 2+ Acceptor substitution can improve the material's anti-reduction properties. 2+ It can inhibit grain growth and promote the formation of a "core-shell" structure, thus effectively improving the dielectric temperature stability of barium titanate-based ceramics in an ultra-wide temperature range. 2+ The addition of will cause the Tc peak to shift to the left.
[0033] D2O3 (D contains Y, Ho, Yb, Gd, Dy): D 3+As a typical amphoteric rare earth ion, it can be used for both donor doping and acceptor doping, and produce defect association, reduce the high-temperature dielectric loss factor (tanδ), and improve the life and reliability of anti-reduction ceramic materials.
[0034] Mn3O4: Mn is in +2 and +3 valences. During the reoxidation stage, low-valent manganese ions will be oxidized, reducing the concentration of oxygen vacancies used to compensate for acceptor defects and alleviating high-temperature semiconductivity problems.
[0035] Nb2O5: Nb is doped as a donor element to replace the B-site Ti ions in BaTiO3. The addition of Nb causes the Core peak of the phase change in the high temperature zone of the dielectric material to be depressed and broadened, while the Shell peak of the phase change in the low temperature zone moves toward the low temperature direction.
[0036] V2O5: V ions can effectively inhibit the diffusion of doped ions D and Mg into BaTiO3 grains, change the distribution of doped ions in the grains, and thus form a "core-shell" structure. Therefore, V can increase the intensity of the Curie peak and improve the temperature stability of the capacitor. Multivalent V ions are mainly +3 and +4 in a reducing atmosphere, which can enhance the anti-reduction property of the dielectric material, improve the insulation resistivity, and reduce the dielectric loss.
[0037] Beneficial effects:
[0038] The present invention adopts BaTiO3-Mn3O4-MgCO3-D2O3-BaCO3-Nb2O5-V2O5 system to prepare ceramic dielectric materials, adds a small amount of submicron or nanometer-level silicon, magnesium, manganese, calcium, niobium, vanadium compounds, and two or more rare earth element oxides such as yttrium, ytterbium, holmium, etc. into barium titanate synthesized by solid phase method, mixes them evenly by wet method, and obtains dielectric porcelain material for MLCC through a series of processes. During the calcination process of dielectric ceramics, some additives will promote the formation of shell-core structure of ceramic grains, inhibit the further growth of barium titanate grains, improve the temperature characteristics of dielectric ceramics, and its temperature stability meets the X6S dielectric material standard formulated by the American Electronic Industry Association; barium titanate is prone to high-temperature oxygen loss and becomes a semiconductor when sintered in a reducing atmosphere, and magnesium, calcium, manganese, niobium, vanadium and other compounds act as acceptors during the calcination process of the ceramic dielectric, and the oxygen vacancy concentration caused is greater than the oxygen vacancy concentration formed by oxygen volatilization, so that barium titanate can also maintain a high electrical insulation resistivity when sintered in a reducing atmosphere. Therefore, the dielectric ceramic material of the present invention has both good high-temperature impedance characteristics and low dielectric loss factor (tanδ).
[0039] On the other hand, through reasonable sintering temperature, sintering atmosphere and sintering time, the ceramic body has good density, suitable core-shell structure and uniform particle size, thus ensuring that the prepared multilayer ceramic capacitor has excellent dielectric properties and capacitance-temperature characteristics.
[0040] The prepared multilayer ceramic capacitor has both X6S characteristic temperature stability and high capacitance, and has high IR characteristics and low dielectric loss factor (tanδ) even in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a flow chart for preparing MLCC of the present invention;
[0043] Figure 2 This is a schematic diagram of the structure of MLCC. DETAILED DESCRIPTION
[0044] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0045] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.
[0046] Example 1
[0047] Mix 100 parts by mass of barium titanate particles with an average particle size of 0.15 μm to 0.25 μm, a certain part by mass of a dopant (its composition is shown in Table 1), 1 part by mass of polyethylene oxide, and 60 parts by mass of an ethanol / toluene mixed solvent, and grind them in a ball mill for 5 hours, with a 0.3 mm zirconium ball and a grinding speed of 50 rpm to obtain a powder mixture slurry. Then add 25 parts by mass of a PVB binder and 1 part by mass of a plasticizer DOA to the powder mixture slurry, mix them evenly, and obtain a ceramic slurry. The obtained ceramic slurry is subjected to the above-mentioned steps of coating film, inner electrode printing, stacking, water pressure, cutting, and debinding to obtain a capacitor green embryo. The capacitor embryo was sintered at 1270°C for 2 hours in a 2% H2-N2 atmosphere with a heating and cooling rate of 3°C / min. Then, it was chamfered, copper plated, sintered at 700-800°C under nitrogen protection, and electroplated to obtain MLCC ceramic capacitors for the evaluation test described below. The evaluation results are listed in Table 1 below.
[0048] Examples 2-3 and Comparative Examples 1-4
[0049] Examples 2-3 and Comparative Examples 1-4 were all manufactured in a similar manner to Example 1. The difference is that the amount of dopant or the sintering conditions were changed in Examples 2-3 and Comparative Examples 1-4. The specific conditions and evaluation results are shown in Table 1 below.
[0050] Table 1
[0051]
[0052] Referring to Table 1, compared with Comparative Examples 1-4, the capacitance temperature change rate of the dielectric ceramic materials of Examples 1-3 at -55°C to 105°C is not greater than ±22%, and the dielectric constant is greater than 3000, and the dielectric loss factor is less than 6.50%. It can be seen that the dopant containing a specific composition and specific sintering conditions can reduce the capacitance temperature coefficient of the prepared dielectric ceramic material, increase the dielectric constant and reduce the dielectric loss factor.
[0053] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance, characterized in that: The steps include: S1, mixing and grinding barium titanate, a dopant, a dispersant, and a solvent to obtain a powder mixture slurry; S2, adding a binder and a plasticizer to the mixture slurry to form a ceramic slurry; S3, applying the obtained ceramic slurry to form a ceramic film; S4, printing an inner electrode on the ceramic film; S5, stacking the ceramic films printed with the inner electrode patterns to obtain a green embryo block; S6, pressing the green embryo block to be compacted by isostatic hydropressure; S7, cutting the compacted green embryo block to obtain a capacitor green embryo; S8, removing the glue from the capacitor embryo to remove organic matter; S9, sintering the capacitor green body after debinding into porcelain; S10, rolling and chamfering the fired capacitor ceramic body to expose the inner electrode and reduce the surface stress of the ceramic body; S11, copper-plating the two ends of the chamfered capacitor ceramic body to connect the inner and outer electrodes; S12, sintering at 700-800℃ under nitrogen protection; S13. Nickel and tin are sequentially plated on the copper end surface to obtain a high-capacitance multilayer ceramic capacitor with X6S characteristics.
2. The method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance according to claim 1, characterized in that: Based on 100 parts by mass of barium titanate, the dopant includes the following components in parts by mass: SiO2 added in an amount of 1.0 to 2.0 parts by mass, MgCO3 added in an amount of 0.5 to 0.7 parts by mass, Mn3O4 added in an amount of 0.04 to 0.06 parts by mass, BaCO3 added in an amount of 1.5 to 2.5 parts by mass, Nb2O5 added in an amount of 0.2-0.5 parts by mass, V2O5 added in an amount of 1.2 to 1.5 parts by mass and rare earth oxide added in an amount of 0.8 to 1.2 parts by mass.
3. The method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance according to claim 2, characterized in that: In the rare earth oxide D2O3, D is any one or more of Y, Ho, Yb, Gd, and Dy.
4. The method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance according to claim 2, characterized in that: The dispersant includes polyethylene oxide resin, and the added amount of the dispersant is 0.5 to 2 parts by weight.
5. The method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance according to claim 2, characterized in that: The solvent includes water, ethanol and / or toluene, and the added amount of the solvent is 60 to 80 parts by weight.
6. The method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance according to claim 2, characterized in that: The grinding in S1 is performed using a ball mill, the grinding balls are 0.2-0.4 mm zirconium balls, the grinding speed is 40-80 rpm, and the grinding and mixing time is 4-6 hours.
7. The method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance according to claim 2, characterized in that: The binder includes polyvinyl butyral resin, and the added amount of the binder is 20 to 30 parts by weight; the plasticizer includes dioctyl adipate, and the added amount of the plasticizer is 0.5 to 2 parts by weight.
8. The method for preparing a multilayer ceramic capacitor with X6S characteristics and high capacitance according to claim 2, characterized in that: In the S9, the sintering temperature is 1265-1275° C., the sintering atmosphere is 1.8-2.2% H2-N2 by volume, and the sintering time is 1.7-2.3 hours.
9. A multilayer ceramic capacitor with X6S characteristics and high capacitance, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Patent Citations
Environmentally friendly high-voltage ceramic capacitor dielectric material and preparation method thereof
CN107226697A
Manufacturing process of vertical ceramic patch capacitor and capacitor product of vertical ceramic patch capacitor
CN108281283A
Dielectric paste and preparation method and application thereof
CN115223793A
High-capacity multi-layer BME ceramic dielectric capacitor prepared based on precursor pre-sintering method and manufacturing method of high-capacity multi-layer BME ceramic dielectric capacitor
CN116947483A
Preparation method of ultrahigh-voltage multilayer chip ceramic capacitor
CN117275942A
Cited By
Ceramic capacitor containing protective layer and preparation method thereof
CN122599278A